Standardization of ethanol extracts from pomegranate fruit peels (Punica Granatum L.) using the reflux method - Wulandari; Ardiantika, Nuri (Journal of Health Management and Pharmacy Exploration, 2026)
Pomegranate peel (Punica granatum L.) is known to contain various active secondary metabolite compounds that have potential in the field of pharmacy. To ensure the quality, safety, and consistency of extracts as raw materials for traditional medicines, a standardization process is required that includes specific and nonspecific parameters. This study aims to standardize pomegranate peel extract and identify the active compounds it contains. Extraction was performed using the reflux method with 96% ethanol solvent. The specific parameters tested included organoleptic properties, water-soluble and ethanol-soluble extract levels, and identification of active compounds through phytochemical testing. The results showed that pomegranate peel extract met the quality standards for extracts with good specific and non-specific characteristics. The extract yield was 12.76%. The results of testing the non-specific parameters of water content, drying loss, ash content, and acid-insoluble ash content were 3.12%, 1.24%, 0.33%, and 0.19%, respectively. Specific standardization includes water-soluble extract content of 3.2% and ethanol-soluble extract content of 4.4%. Phytochemical testing of the extract showed the presence of active compounds such as alkaloids, flavonoids, saponins, tannins, quinones, and steroids.